KARBON TERSIMPAN DALAM PRODUK KAYU SENGON MENGGUNAKAN BEBERAPA MODEL OKSIDASI - Yonky Indrajaya (Jurnal Agroforestri Indonesia, 2019)
Harvested wood product is one of the carbon pools that must be considered in calculating carbon emission from forestry sector. There are several models of wood product retirement : linear, logistic, and exponential. The type of model applied inthe calculation of wood product pool influence the estimated amount of carbon stored in wood product, and hence also influence the recommended management regime of a plantation forest. This study analyzed  how different models of wood product oxidation produced different estimates of carbon stored in sengon wood product and caused different management recommendation of sengon plantation. The models used in this paper include linear (VCS model), exponential (IPCC, 2006), and logistic (Miner model). The focus of the study is to evaluate only long term wood product that is oxidized up to 100 years. The study showed that the lowest carbon stored  from sengon  wood product are those estimated by linear, logistic, and exponential respectively. VCS model with 20 years linear decay is conservative.